SEMEN PADANG DAN POLITIK EKONOMI KOLONIAL - Gusti Asnan (Balai Pelestarian Nilai Budaya Sumatera Barat, 2019)
This article looks at the history and development of Padang Cement Fabric in its relationship with the Dutch economic policy by the end of the 19th C. and in the beginning of the 20th C. The foundation of the oldest cement fabric in Indonesia had a close relationship with political-economic policy introduced by the Dutch colonial government, which gave many opportunities to the foreign investors to exploit its colony. Padang Cement Fabric itself only one of several fabrics, minings, and big plantations in which the investors invested their capital during the liberal era in West Sumatra. The construction of Padang Cement Fabric also represented colonial government policy in urban planning in Padang municipality. In the beginning of the 20th C., the development orientation of Padang was directed to the eastward and southward of the city. Besides that, to encourage the investors and to implement its urban planning policy, colonial government provided special supports, such as introducing regulations to reduce administrative process for investors to invest their money in this region. The government even sacrificed the native peoples in order to succeed its colonial political-economic.